EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION AND LOYALTY PT. JIWASRAYA INSURANCE (PERSERO) PADANG BRANCH. SUPERVISED - Hasri, Mulya; Samsir, Samsir; ZA, Kasman Arifin (Jurnal Tepak Manajemen Bisnis, 2019)
The level of competition in the insurance industry is currentlyincreasingly showing improvement. This is seen from the number of companiesoffering life insurance services in Indonesia, especially in Padang, West Sumatra.Therefore, to be able to survive in the life insurance industry, Jiwasraya must beable to maintain customers and increase the number of customers. One strategy isto improve service quality. Because this will be able to shape customersatisfaction and loyalty.This research will be carried out by the Jiwasraya insurance customer inPadang Branch. Research location spread in the Padang Branch Area, with asample of 100 customers. The data collection technique used is using aquestionnaire. Whereas for analyzing data, the SPSS 17.00 for Windows andSmartPLS programs are used.The results of this study indicate that: 1) service quality affects thesatisfaction of Jiwasraya insurance customers 2) service quality affects the loyaltyof Jiwasraya's insurance customers; 3) customer satisfaction affects the loyalty ofJiwasraya insurance customers, 4) service quality affects the loyalty ofJiwasraya's insurance customers through customer satisfaction.Based on the results of the study, the company must be able to increasecustomer satisfaction, one of which is to improve and improve the quality of services provided to customers.